Computational analysis of fluid flow past a bluff body at low reynolds number in different Apex Angle / M.Z.M. Jusoh, Nur Ain A.R and Muhammad Wafi Md Nor - Jusoh, M.Z.M.; A.R, Nur Ain; Md Nor, Muhammad Wafi (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
A computational fluid dynamic analysis (CFD) is presented in the study of low Reynolds number fluid flow moving past bluff bodies. The study is focusing on the understanding of the effects of the apex-angles orientation on the flow structure and related occurring force. The apex-angle both facing upstream and downstream were computationally investigated. The simulation results of the cylinder solid are compared with available experimental data to justify the results and the model used. Results obtained in the present work were Strouhal number, drag coefficient, and Fast Fourier Transform (FFT). The study had found that the value of the drag force is increasing directly proportional to the apex angle. In contrast, the value of Strouhal number inversely proportional to the increasing of the apex angle. This was due to the flow over a cylinder creating a vortex shedding in the wake region which influenced the flow separation of fluid. Through the changing on orientation of the apex angle, it was also found that the characteristic linear dimension of the geometry will also be changed, thus affecting the flow pattern.